Pits of Date Palm: Bioactive Composition, Antibacterial Activity and Antimutagenicity Potentials - Samy Selim; Mohamed Abdel-Mawgoud; Tarak Al-sharary; Mohammed S. Almuhayawi; Mohammed H. Alruhaili; Soad K. Al Jaouni; Mona Warrad; Hussein S. Mohamed; Nosheen Akhtar; Hamada AbdElgawad (Agronomy, 2021)
Palm date pits as a source of bioactive chemicals have received only a limited amount of attention. This study was conducted to determine the bioactive components of Ajwa date pits, as well as their antibacterial and antimutagenic activities. Therefore, chromatographic techniques were used to extract and isolate the phenolic compounds in date pits, which were further elucidated by using spectroscopic techniques (FTIR and NMR) for identification of most abundant bioactive metabolites. Data showed that the methanolic extract of date pits contained high levels of total phenols (17.38 mg GA/g) and flavonoids (5.324 mg QE/g). The HPLC analysis of date pits’ extract showed the presence of six phenolic compounds. Interestingly, there was a significant amount of gallic acid (11.85 mg GA/gFW), which was isolated via chromatography (thin layer chromatography) and identified by spectroscopic investigation (FTIR, MS, 1H, and 13C NMR). An inhibitory effect on Gram-positive and Gram-negative bacteria was observed for date pit gallic acid purified. S. aureus cell viability was completely inhibited at 200 µg/mL of acid for 6 h. Moreover, gallic acid was found to have a significant antimutagenic activity against Salmonella typhimurium at all tested concentrations, with a decrease in percent mutagenicity from 52 to 32 in the case of test substance TA98, and from 39 to 15 for test substance TA100 in terms of percent antimutagenicity. Gallic acid at a dose of 3000 g/plate had the greatest antimutagenic effect on S. typhimurium TA98, with the lowest toxicity. Overall, the bioactive properties of date pits’ extracts were investigated, with a particular attention to their chemical composition, biological activity, and pharmaceutical applications.